Measuring the BNF of Soybean Using 15N-Labelled Urea with Different Atom Excess (A.E.) Content - A. Citraresmini; H. Halim; E.L. Sisworo (Atom Indonesia, 2012)
The soybean is a legume which has an ability to supply its major nitrogen need by the biological nitrogen fixation (BNF) process. This process is made possible by nodules formed in their roots, colonized by Rhizobium sp.bacteria. An accurate estimation of N gained by BNF is necessary to predict the increase or decrease of chemical fertilizer-N requirements to increase soybean production. Among several methods, the 15N method was used to estimate the ability of legumes to perform BNF. The study involved soybean var. Willis (W) and a completely non-BNF soybean var. CV, which is termed as a standard crop. The standard crop is non-nodulated soybean, but it has the same main physiological traits with var. Willis. The aim of this study was to determine whether15N-labelled fertilizer with different %a.e. given to nodulated and non-nodulated soybean would not be of significant consequences for the calculation of N-BNF of W. The treatments applied were different rates of urea (20 kg N/ha and 100 kg N/ha) combined with different atom excess percentages (%a.e.)15N (2% and 10%). Thus, the combination of treatments were as follows:(1) W-ll (20 kg N; 2% a.e); (2) CV-hl (100 kg N; 2% a.e); (3) W-lh (20 kg N; 10% a.e); (4) CV-hh (100 kg N; 10% a.e); (5) CV-ll (20 kg N; 2% a.e); (6) W-hl (100 kg N; 2% a.e); (7) CV-lh (20 kg N; 10% a.e); (8) W-hh (100 kg N; 10% a.e). The result of the experiment showed that a high %a.e. with a low rate of 15N and a low %a.e. with a high rate of N should be used to study the %N-BNF of nodulated plants.Received: 16 March 2012; Revised: 14 December 2012; Accepted: 17 December 2012